e-LKPD IPA Berbasis Contextual Teaching and Learning (CTL) Materi Pencemaran Lingkungan - Hasanah, Daimul; Laily Rochmawati Listiyani; Saputri, Apriani Rahayu (Wacana Akademika: Majalah Ilmiah Kependidikan, 2024)
This research aims to produce science electronic student worksheet based on Contextual Teaching and Learning (CTL) on environmental pollution material, determine the quality of the electronic student worksheet that has been developed, and determine students' responses to the electronic student worksheet that has been developed. According to Thiagarajan, this type of research includes research and development with the 4D development model through the Define, Design, Develop stages. Observation, interview, and questionnaire techniques were used to collect data, while data collection instruments had observation sheets, interview sheets, expert assessment sheets and student response questionnaire sheets. The V-Aiken index and descriptive data analysis were used to analyze the data. The results of this research include: a CTL-based science electronic student worksheet on environmental pollution material for seventh grade middle school students has been produced through the development stages of define, design, develop; the quality of the science electronic student worksheet is declared valid with high criteria; and students responded very agreeably to the CTL-based science electronic student worksheet. Thus, the CTL-based science electronic student worksheet has met the eligibility criteria as junior high school science teaching materials.